A Novel Method to Generate and Expand Clinical-Grade, Genetically Modified, Tumor-Infiltrating Lymphocytes - Forget, Marie-Andrée; Tavera, René J.; Haymaker, Cara; Ramachandran, Renjith; Malu, Shuti; Zhang, Minying; Wardell, Seth; Fulbright, Orenthial J.; Toth, Chistopher Leroy; Gonzalez, Audrey M.; Thorsen, Shawne T.; Flores, Esteban; et al. (Frontiers in Immunology, 2017)
Following the clinical success achieved with the first generation of adoptive cell therapy (ACT) utilizing in vitro expanded tumor-infiltrating lymphocytes (TIL), the second and third generations of TIL ACT are evolving towards the use of genetically-modified TIL. TIL therapy generally involves the transfer of a high number of TIL, ranging from 109 to 1011 cells. One of the technical difficulties in genetically modifying TIL, using a retroviral vector, is the ability to achieve large expansion of transduced TIL, while keeping the technique suitable to a GMP (Good Manufacturing Practices) environment. Consequently, we developed and optimized a novel method for the efficient production of large numbers of GMP-grade, gene-modified TIL for the treatment of patients with ACT. The chemokine receptor CXCR2 was used as the gene of interest for methodology development. The optimized procedure is currently used in the production of gene-modified TIL for two clinical trials for the treatment of metastatic melanoma at MD Anderson Cancer Center.